Association of remnant cholesterol with cardiovascular events and mortality in biopsy-proven diabetic kidney disease - Hu, Qiyuan; Chen, Ling; Xing, Lingzhi; Xu, Yamei; Xiong, Jiachuan; Tang, Yuewu (Frontiers in Endocrinology, 2026)
BackgroundRemnant cholesterol (RC) has been recognized as a critical risk factor for vascular diseases. However, its association with cardiovascular disease (CVD) and overall mortality in individuals with diabetic kidney disease (DKD) has not been thoroughly investigated.MethodsThis retrospective single-center study enrolled 329 patients with biopsy-confirmed DKD from August 2009 to December 2018. The prognosis of patients with varying RC levels was compared. In addition, the association between RC levels and left ventricular structure and function was examined. Furthermore, the predictive capability of RC for clinical outcomes was assessed.ResultsOver the follow-up period, 76 patients (23.1%) experienced CVD events, while 44 patients (13.4%) died. Kaplan-Meier analysis demonstrated that patients in the high RC group exhibited significantly elevated rates of CVD events (p = 0.0047) and all-cause mortality (p = 0.0213). Additionally, multivariate Cox regression analysis confirmed RC as an independent risk factor for CVD events (HR = 1.323, 95% CI 1.076-1.626, p = 0.008) and overall mortality (HR = 1.359, 95% CI 1.039-1.779, p = 0.025). Finally, the AUC analysis indicated that the inclusion of RC in traditional risk factors improved their predictive accuracy.ConclusionRC independently contributes to the risk of CVD events and all-cause mortality in individuals with biopsy-confirmed DKD.